Chrysanthemum indicum and chrysanthemum morifolium: chemical composition of their essential oils and their potential use as natural preservatives with antimicrobial and antioxidant activities - Youssef, Fadia S.; Eid, Safaa Yehia; Alshammari, Elham; Ashour, Mohamed L.; Wink, Michael; Readi, Mahmoud Zaki el (Foods, 2020)
The composition of essential oils of Chrysanthemum indicum and C. morifolium were comparatively studied using both Gas Chromatography/Flame ionization Detector (GC/FID) and Gas Chromatography/Mass spectrometry (GC/MS) analyses. The antiviral activity was determined using a plaque reduction assay against three common viruses namely, herpes simplex type-1 (HSV-1), hepatitis A (HAV) and vesicular stomatitis virus (VSV). The antimicrobial activity was assessed using agar diffusion and microdilution methods and the minimum inhibitory concentration (MIC) values were determined. In addition, the anti-mycobacterial evaluation was carried out using the Alamar blue assay and the effect against Helicobacter pylori was investigated. The anti-trypanosomal activity was evaluated using the resazurin method. GC investigations revealed that camphor is the major constituent of both oils accounting for 36.69 and 14.56% in the essential oils from C. indicum and C. morifolium, respectively. C. indicum was biologically more active in all experiments; it exhibited a notable antitrypanosomal activity with an IC50 value equals 45.89 μg/mL and a notable antimicrobial activity versus Streptococcus agalactiae with a MIC value of 62.5 μg/mL. It also inhibited the replication of VSV with an IC50 value of 3.14 μg/mL. Both oils revealed antioxidant potential with IC50 values of 2.21 and 2.59 mg/mL for C. indicum and C. morifolium, respectively. This study provides evidence beyond the traditional use of both Chrysanthemum indicum and C. morifolium as anti-infective agents. Thus they could be used as spices in food and can be incorporated in different food products and pharmaceutical preparations as natural preservatives possessing antioxidant potential.
Gesehen am 26.11.2020